Rapidity of response to hypoxic conditions during exercise - Harris, K. B. H.; Foster, C.; de Koning, J. J.; Dodge, C.; Wright, G.; Porcari, J. P. (International Journal of Sports Physiology and Performance, 2013)
Previous studies have found decreases in arterial oxygen saturation to be temporally linked to reductions in power output (PO) during time-trial (TT) exercise. The purpose of this study was to determine whether preexercise desaturation (estimated from pulse oximetry [SpO2]), via normobaric hypoxia, would change the pattern of PO during a TT. Purpose: The authors tested the hypothesis that the starting PO of a TT would be reduced in the EARLY trial secondary to a reduced SpO2 but would not be reduced in LATE until ~30 s after the start of the TT. Methods: Eight trained cyclists/triathletes (4 male, 4 female) performed 3 randomly ordered 3-km TTs while breathing either room air (CONTROL) or hypoxic air administered 3 min before the start of the TT (EARLY) or at the beginning of the TT (LATE). Results: There was no effect of hypoxia on PO during the first 0.3 km of either the EARLY or the LATE trial compared with CONTROL, although there was a significant decrease in pre-TT SpO2 in EARLY vs CONTROL and LATE. The time for PO to decrease was ~40 s after the start of the TT in both EARLY and LATE. Conclusions: The results support the strong effect of the preexercise template on the pattern of PO during simulated competition and suggest that reductions in SpO2 are not direct signals to decrease PO.